Impact of Human Resource strategies on Perceived Organizational Support at Jordanian Public Universities (Global Journal of Management and Business Research, 2017)
The study aimed to identify the effect of Human Resource strategies on perceived organizational support at public Jordanian Universities such that factors that may assist in improving or worsening work performance can be identified, moreover. The population of the study was all the universities administrative staff in northern Jordanian public universities with 4908 staff members. The random sample of the study was 350 staff members (7%) of the study population. The study included a number of results, Among which the existence of a statically significant effect of the human resources strategies (human resource planning, appointment and selection, training and development, incentives#x2019; and rewards and performance evaluation on perceived organizational support.
Keywords: human resource strategies; perceived organizational support; public universities; jordan